NEWLY CONSTRUCTED TESTS FOR REPETITIVE STRENGTH EVALUATION IN JUDO - Janoš Kopas (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
On a sample of 89 men, age between 16 and 19, who have trained judo for at least three years, newly constructed tests have been applied for specific motion ability evaluation. Subject of research are metric characteristics of these tests, and the aim of research is to enrich the theory and practice of judo sport with new cognition. Based on the knowledge of structure of motion in judo, tests have been developed that measure specific motion ability under influence of excitation duration mechanism, and as isolated factor can be interpreted as a factor of specific repetitive strength. With the aim to establish reliability, Cronbach's Alpha factor has been calculated as well as Guttman's lambda 3 & 6 coefficient. To establish factor validity of tests, factor analysis has been performed where number of significant components has been determined by Guttman - Kaiser criterion.